2010
DOI: 10.1152/ajplung.00281.2009
|View full text |Cite
|
Sign up to set email alerts
|

JNK regulates serotonin-mediated proliferation and migration of pulmonary artery smooth muscle cells

Abstract: JNK is a member of the MAPK family and has essential roles in inflammation and cell differentiation and apoptosis. In recent years, there have been accumulating data indicating a novel role for JNK in cell growth and migration. In this report, we demonstrate that JNK activity is necessary for serotonin (5-HT)-induced proliferation and migration of bovine pulmonary artery smooth muscle cells (PASMCs). Stimulation with 5-HT was found to lead to activation of JNK with a maximal activation at 10 min. Inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 26 publications
5
21
1
Order By: Relevance
“…Moreover, p21 CIP1 and p27 KIP1 , two important CDKIs, almost inhibit transition of the cell cycle at all stages. Therefore, their of JNK is a critical molecule in PASMC proliferation and tumor cell growth ( 32,33 ). In the present study, we observed that EETs promote the nuclear translocation of JNK and activate the JNK/c-Jun pathway, leading to the increase of PAEC growth and angiogenesis.…”
Section: Eets Inhibit Apoptosis Of Pulmonary Artery Smooth Muscle Celsupporting
confidence: 57%
“…Moreover, p21 CIP1 and p27 KIP1 , two important CDKIs, almost inhibit transition of the cell cycle at all stages. Therefore, their of JNK is a critical molecule in PASMC proliferation and tumor cell growth ( 32,33 ). In the present study, we observed that EETs promote the nuclear translocation of JNK and activate the JNK/c-Jun pathway, leading to the increase of PAEC growth and angiogenesis.…”
Section: Eets Inhibit Apoptosis Of Pulmonary Artery Smooth Muscle Celsupporting
confidence: 57%
“…Additionally, PDGF-induced TKT loss occurred in the presence of a PI3K, ERK and p38 inhibitor, but was not noted in the presence of a specific inhibitor of Akt that did not impact PI3K and of JNK that did not impact p38. These results indicate that PDGF induced loss of TKT via a signal pathway involving PI3K-independent Akt and JNK and are consistent with reports of a PI3K-independent Akt activation pathway [42] and of Akt crosstalk with JNK [43, 44]. …”
Section: Discussionsupporting
confidence: 92%
“…In addition, the p38MAPK and ERK regulated the cell cycle progression, which increased medial thickening and leads to vascular remodeling. Besides, time that the MAPK signaling pathways participate in the pathological process of hypoxiaPrevious reports have showed that 5-hydroxytryptamine (5-HT) stimulated PASMCs proliferation and migration by activating JNK [24]. However, our results identify that there were no changed in the expression of p-JNK in the pulmonary arterial from both PAH patients and rat PAH models.…”
Section: Discussioncontrasting
confidence: 57%
“…JNK/stress activated protein kinase (SAPK) is response to growth factors, cytokines, environmental stress, ultraviolet light, oxidative stress, and heat shock [19][20][21][22][23]. It has been shown that activation of JNK by 5-hydroxytryptamine results in the enhanced proliferation and migration of pulmonary arterial smooth muscle cells (PASMCs) [24]. Recent studies apoptosis as well as differentiation of s mesenchymal stem cells [25][26][27].…”
Section: Introductionmentioning
confidence: 99%